PENANGANAN MASALAH MENTAL EMOSIONAL PADA ANAK USIA SEKOLAH - Jumaini; Dinda Daisya Putri; Elsa Amanda Putri; Harni Safitri Harahap; Miftahul Ilmi; Nida Rahmatul Adhani; Raesa Audya Agusty; Estomihi Sitinjak; Francco Nero; Harun; Rofil Rahmat Hidayat (Nusantara Hasana Journal, 2022)
Mental health problems can be a risk factor for mental distress and psychopathology in the future. Mild emotional mental disorders have a 4.1 times greater risk of having a poor quality of life compared to people who do not have emotional mental disorders. By looking at the high cases of emotional mental disorders, especially in children in Indonesia, this is the background of this research, through the title Handling Emotional Mental Problems in School-Age Children. This activity is in the form of socialization on the handling of Mental Emotional Problems in School Age Children in July 2022. It was attended by 25 school-age children aged 8 to 12 years. The method of this socialization activity is by presenting material about bullying containing forms of bullying, factors, impacts, and others. After delivering the material, the activities of management and handling of anxiety and stress in school-age children were continued by demonstrating deep breathing techniques. The results obtained were that the children were very enthusiastic in answering the question session at the end of the socialization. Of the 25 children who attended, 20 children were able to answer the questions given by the speaker. So that the success of delivering material about bullying to school-age children was successfully conveyed. Several things that can be concluded from this community service activity are that in general children have grown and developed well. But of course its growth is influenced by environmental conditions. So it is not uncommon for children to be easily influenced by the times and follow the bad things they see.